Comment on "A Comparison of Buprenorphine + Naloxone to Buprenorphine and Methadone in the Treatment of Opioid Dependence during Pregnancy: Maternal and Neonatal Outcomes" - Robert G. Newman M.D., M.P.H; Susan G. Gevertz A.B (SAGE Publishing, 2013)
In a recent article, Lund et al sought to compare maternal and neonatal outcomes of various treatment regimens for opioid dependence during pregnancy. 1 In their background, discussion the authors state that "In the United States buprenorphine plus naloxone [Suboxone®] ... has been the preferred form of prescribed buprenorphine due to its reduced abuse liability relative to buprenorphine alone [Subutex®]." This claim is certainly consistent with the view of the firm that has manufactured and sold both products, Reckitt Benckiser. In September of 2011, the company announced that it was "... discontinuing distribution and sale of Subutex® tablets as we believe that mono product (product containing buprenorphine alone with no naloxone) creates a greater risk of misuse, abuse and diversion ...". 2 Supporting evidence for the alleged "reduced abuse liability" appears to be lacking, however, and evidence cannot be located in the two references cited by Dr. Lund and his co-authors, which in fact are silent on the subject of abuse potential. 3 , 4 In contrast, it has been reported that the transition to buprenorphine/naloxone from the mono formulation has been associated with "... no reduction in injection risk behaviors among IDUs." 5